2022
DOI: 10.3389/fpls.2022.982457
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of phenylalanine ammonia-lyase (PAL) multigene family and their differential expression analysis in wheat (Triticum aestivum L.) suggested their roles during different stress responses

Abstract: Phenylalanine ammonia-lyase (PAL) is a key enzyme in the phenylalanine metabolism pathway and plays an important role in plant growth and stress response. It has been widely reported in plants, but less studied in wheat. In this study, 54 PAL genes were identified in the wheat genome. Based on phylogenetic analysis, the 54 TaPAL genes were divided into four groups (I, II, III, and IV). Then, the expression levels of TaPALs under biotic stresses were analyzed by transcriptome data analysis. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 62 publications
(52 reference statements)
6
23
0
Order By: Relevance
“…Monolignol biosynthesis begins with the deamination of phenylalanine through phenylalanine ammonia-lyase (PAL), producing cinnamic acid. Due to its critical role in phenylpropanoid biosynthesis, function of PAL has been extensively studied in various plants ( Wanner et al., 1995 ; Zhu et al., 1995 ; Chang et al., 2008 ; Zhan et al., 2022 ). In Arabidopsis ( Arabidopsis thaliana ), mutation of PAL1 and PAL2 led to a significant decrease in phenylpropanoids and lignin ( Rohde et al., 2004 ).…”
Section: Lignin Biosynthesismentioning
confidence: 99%
“…Monolignol biosynthesis begins with the deamination of phenylalanine through phenylalanine ammonia-lyase (PAL), producing cinnamic acid. Due to its critical role in phenylpropanoid biosynthesis, function of PAL has been extensively studied in various plants ( Wanner et al., 1995 ; Zhu et al., 1995 ; Chang et al., 2008 ; Zhan et al., 2022 ). In Arabidopsis ( Arabidopsis thaliana ), mutation of PAL1 and PAL2 led to a significant decrease in phenylpropanoids and lignin ( Rohde et al., 2004 ).…”
Section: Lignin Biosynthesismentioning
confidence: 99%
“…variabilis [34]. In wheat, silencing of TaPAL32 and TaPAL42 reduces the resistance of wheat to stripe rust [35]. In the transcriptome analyses in the present study, cinnamic acid biosynthesis (GO:0009800) and L-phenylalanine catabolic (GO:0006559) processes were highlighted, both in SHWs and their parents, following FCR infection.…”
Section: Discussionmentioning
confidence: 58%
“…As an entry-point enzyme in the phenylpropanoid biosynthesis pathway, PAL converts phenylalanine to trans-cinnamic acid and free ammonia, thereby playing an important role in lignin and salicylic acid biosynthesis. Many studies have shown that PAL acts as a positive regulator of resistance to various plant biotic stresses [ 30 – 36 ]. In the transcriptome analyses in the present study, cinnamic acid biosynthesis (GO:0009800) and L-phenylalanine catabolic (GO:0006559) processes were significantly enriched both in SHWs and their parents following FCR infection.…”
Section: Discussionmentioning
confidence: 99%